Role of foliar iron in modulating primary and antioxidant mechanisms of Mentha piperita L. under different light conditions - Custódio de Moura Gonçalves, Fabrício [UNESP]; Benetti Mantoan, Luís Paulo [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (Taylor & Francis, 2025)
The present study aims to uncover the role of foliar iron in modulating primary and antioxidant mechanisms of Mentha piperita L. under light conditions. Plants were distributed in a completely randomized design and submitted to five Fe concentrations; 0 (control), 0.5, 1.0, 1.5 and 2.0 g L−1. And under two irradiance conditions; I100% (full sun) and I50% (50% irradiance). Forty-eight hours after foliar Fe application, the following parameters were determined: gas exchange, chlorophyll (a and b), carotenoids and anthocyanin content, chlorophyll a fluorescence, peroxidase and superoxide dismutase activities. The highest Fe concentrations affect the internal CO2 concentration (Ci) and water use efficiency, according to the photochemical extinction coefficient and peroxidase and superoxide dismutase activities. I100% increased the minimum dark-adapted leaf fluorescence and electron transport rate, while, I50% increased the chlorophyll values, and carotenoid content, Ci and transpiration, maximum dark-adapted leaf fluorescence, antenna quantum efficiency and dark-adapted fluorescence. We discovered that isolated treatments are more effective in modifying the response mechanisms of M. piperita plants and the interaction of Fe and irradiance tends to alter antioxidant metabolism.
Keywords: Light; medicinal plant; metabolites; micronutrient; productivity